Sex Moderates Amyloid and Apolipoprotein ε4 Effects on Default Mode Network Connectivity at Rest - Caldwell, Jessica Z. K.; Zhuang, Xiaowei; Leavitt, MacKenzie J.; Banks, Sarah J.; Cummings, Jeffrey; Cordes, Dietmar; , The Alzheimer's Disease Neuroimaging Initiative (Frontiers in Neurology, 2019)
Women are more likely to have Alzheimer’s disease (AD) and decline more rapidly once diagnosed despite greater verbal memory early in the disease compared to men—an advantage that has been termed “memory reserve.” Resting state functional MRI (fMRI) investigations demonstrate interactions between sex and AD risk factors in default mode network (DMN), a network of brain regions showing progressive dysfunction in AD. Separate work suggests connectivity of left prefrontal cortex (PFC) correlates with general cognitive reserve in healthy aging. It is unknown whether left prefrontal functional connectivity with anterior and posterior default mode network (aDMN, pDMN) might differ by sex in AD. This study employed group independent component analysis (ICA) to analyze resting state fMRI data from 158 participants from the Alzheimer's Disease Neuroimaging Initiative (ADNI) with baseline diagnoses of normal cognition or early mild cognitive impairment (eMCI). pDMN and aDMN were defined on a subject-specific basis; prefrontal areas were selected from the Brodmann atlas (BA 6, 44, 8, and 9). Moderation regression analyses examined whether sex and amyloid PET positivity (A+/-) moderated effects of apolipoprotein Ɛ4 (APOE ε4) on connectivity between left PFC, aDMN, and pDMN; and between aDMN and pDMN. Significant analyses were followed up with partial correlations assessing relationship of connectivity to memory on the Rey Auditory Verbal Learning Test (RAVLT), and with preliminary analyses within NC and eMCI groups. Results showed no sex moderation of effects of A+ and APOE ε4 on left prefrontal/DMN connectivity in the full sample. However, sex significantly moderated impact of A+ and APOE ε4 on connectivity between aDMN and pDMN (p < 0.01). Women with an APOE ε4 allele and A+ showed greater aDMN/pDMN connectivity than their E4- counterparts. No significant results were observed in men. Subgroup analyses suggested the aDMN/pDMN finding was true for NC, not eMCI. Partial correlations controlling for age and education showed increased aDMN/pDMN connectivity related to better verbal learning in women (p < 0.01) and not men (p = 0.18). In women at risk for AD or in early symptomatic stages who also have evidence of amyloid burden, stronger aDMN/pDMN connectivity may support verbal learning.